Application of high-performance liquid chromatography for the analysis and pharmocokinetics of mephenoxalone - Van der Westhuizen, Fiona (Rhodes University, Faculty of Pharmacy, Pharmacy, 1988)
Mephenoxalone is a mild central nervous system depressant with activity resembling that of meprobamate. Since its introduction in 1961 mephenoxalone has been used as an anxiolytic and as a muscle relaxant, although the latter effect is weak. Preliminary studies on the absorption and disposition of mephenoxalone have been conducted in beagle dogs but no pharmacokinetic data from human studies have been reported, except for a single study in which the biotransformation products present in human urine were identified. Methods presently available for the determination of mephenoxalone in biological fluids lack the sensitivity, specificity and precision required for detailed pharmacokinetic studies. In this study, a rapid, sensitive, precise reverse-phase high-performance liquid chromatographic method with ultraviolet detection at 200nm was employed for the determination of mephenoxalone in biological fluids. Serum and urine samples were prepared for chromatographic analysis using simple liquid-liquid extraction techniques. The application of the assay to pharmacokinetic studies in humans is presented. After administration of a single oral dose of 400mg mephenoxalone dispersed in 150ml water to six young, healthy volunteers, the compound was rapidly absorbed with the peak concentration of 8Î¼g/ml occurring after about 1 hour. The elimination half-life was approximately 3 hours. The drug was extensively metabolized with only about 1 percent of the administered dose being excreted unchanged in the urine after 24 hours. The bioavailability of a newly developed mephenoxalone-containing tablet was also investigated. The drug was absorbed more rapidly from the tablet than from the dispersed dose. This was attributed to a shorter in vivo dissolution time on the basis of in vitro tests, but this effect is not expected to be clinically significant. In addition, two human urinary metabolites of mephenoxalone were identified as unconjugated hydroxylated derivatives using thermospray HPLC-mass spectrometry. The plasma protein-binding properties of mephenoxalone were also investigated.
Keywords: High performance liquid chromatography; Central nervous system depressants